Evolution of small inversions in chloroplast genome: A case study from a recurrent inversion in angiosperms - Catalano, Santiago Andres (2009)
Small inversions (SIs) in the chloroplast genome of angiosperms are ubiquitous. These inversions are always flanked by inverted repeats (palindromes or quasipalindromes) between approximately 8 and 50 bp long that form a hairpin structure when the DNA is single-stranded. We evaluated different methodological and empirical issues about SI evolution. As a case study, we analysed an SI recently discovered in the psbC-trnS intergenic region of Prosopis (Fabaceae). First, we analysed how inversions can be optimized in cases where the inverted segment also shows indels and substitutions, proposing a method based on Fixed States Optimization. Second, we evaluated the occurrence of this inversion on a phylogeny that includes the major lineages of angiosperms. Finally, we assessed whether the occurrence of this inversion was related to the thermodynamic stability of the hairpin structure (measured by its corresponding free energy) and/or the length of the palindromes by using a modified version of Maddison's Concentrated Changes Test. Hairpin structure was conserved in most of the 154 sequences analysed, with the inversion taking place at least 10 times in different lineages (monocots, magnoliids, rosids). As was previously proposed for other SIs, our analysis strongly suggests that the occurrence of this inversion is correlated with higher hairpin stability. In contrast, we found no evidence of a correlation with longer palindromes. Our results are in agreement with the hypothesis that hairpin formation is a requisite for SI occurrence. However, alternative explanations cannot be discarded.